Interleukin-8 blockade prevents activated endothelial cell mediated proliferation and chemoresistance of acute myeloid leukemia. (September 2019) - Vijay, Vindhya; Miller, Regan; Vue, Gau Shoua; Pezeshkian, Mida Bahareh; Maywood, Michael; Ast, Allison M.; Drusbosky, Leylah M.; Pompeu, Yuri; Salgado, Alan D.; Lipten, Samuel D.; Geddes, Timothy; Blenc, Ann Marie; et al.
Highlights: AML cells activate endothelial cells (ECs) resulting in secretion of IL-8. Activated EC-derived IL-8 results in expansion and chemoresistance of AML cells. Inhibition of IL-8 decreases AML proliferation and enhances response to therapy. Effects of IL-8 inhibition are through Akt signaling pathways. Abstract: One of the greatest challenges in treating acute myeloid leukemia (AML) is chemotherapy refractory disease. Previously, we demonstrated a novel mechanism whereby AML-induced endothelial cell (EC) activation leads to subsequent leukemia cell adherence, quiescence and chemoresistance, identifying activated ECs as potential mediators of relapse. We now show mechanistically that EC activation induces the secretion of interleukin-8 (IL-8) leading to significant expansion of non-adherent AML cells and resistance to cytarabine (Ara-C). Through crystallography and computational modeling, we identified a pocket within IL-8 responsible for receptor binding, screened for small molecules that fit within this pocket, and blocked IL-8 induced proliferation and chemo-protection of AML cells with a hit compound. Results from this study show a new therapeutic strategy for targeting the sanctuary of an activated leukemia microenvironment.